1984
DOI: 10.1177/016001768400900102
|View full text |Cite
|
Sign up to set email alerts
|

Labor Force Mobility in the United States: Migration, Unemployment, and Remigration

Abstract: "This study examines the relationships between pre- and post-move unemployment and interstate migration of the United States labor force for the period 1965 to 1970. Multivariate analyses are conducted for several large occupation groups. The results indicate a strong link between unemployment and migration. Unemployment increases migration possibilities for each large occupation group considered. Substantial post-move unemployment exists, but there is a significant link between migration and such unemploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 11 publications
5
29
1
1
Order By: Relevance
“…She draws four noteworthy conclusions: (1) the more distant the move, the higher is the probability of a repeat move, presumably because information is less reliable at a distance and (2) when unemployment motivates the initial move, return moves are more likely, presumably because financial pressures tend to impair the effectiveness of job search. This finding is similar to that of Herzog and Schlottmann (1982), which was obtained using 1970 Census PUMS data. (3) Household heads who are very young tend to return soon after their initial move, presumably because they are less experienced in making such important decisions and perhaps less informed about opportunities elsewhere.…”
Section: Other Micro Analysessupporting
confidence: 89%
See 1 more Smart Citation
“…She draws four noteworthy conclusions: (1) the more distant the move, the higher is the probability of a repeat move, presumably because information is less reliable at a distance and (2) when unemployment motivates the initial move, return moves are more likely, presumably because financial pressures tend to impair the effectiveness of job search. This finding is similar to that of Herzog and Schlottmann (1982), which was obtained using 1970 Census PUMS data. (3) Household heads who are very young tend to return soon after their initial move, presumably because they are less experienced in making such important decisions and perhaps less informed about opportunities elsewhere.…”
Section: Other Micro Analysessupporting
confidence: 89%
“…"Using a special tabulation of the 1970 Census PUMS that allows them to identify whether individuals were working full time or part time five years prior to the census, Herzog and Schlottmann (1984) further substantiate DaVanzo's finding. After making adjustments for labor force status, Herzog and Schlottmann are able to infer pre-move unemployment.…”
Section: Other Micro Analysesmentioning
confidence: 80%
“…A ccording to neoclassical economic theory, migration should have an equilibrating effect upon regional differences in wages and unemployment rates (Sjaastad, 1962), and numerous studies have modelled this relationship at both macro-(see Greenwood, 1975;Clark, 1982;Greenwood and Hunt, 1984;Greenwood et al, 1991) and micro-levels (see Herzog and Schlottman, 1984;van Dijk et al, 1989). A recent review of the findings from these types of models (Herzog et al, 1993) suggested that personal unemployment augments migration and that out-migration tends to be increased by higher levels of unemployment, although the evidence for this latter effect is not overwhelming.…”
Section: Introductionmentioning
confidence: 99%
“…They formulate the typical gravity model of interregional migration, but avoid a direct discussion of how the spatial distribution of population can be disturbed. A microdata based study by Herzog and Schlottmann (1984) also presents evidence that both a person's employment status and the overall unemployment rate of their region of residence affect the probability of migrating.…”
Section: (18)mentioning
confidence: 99%